Product Innovation as a Mediator in the Impact of R&D Expenditure and Brand Equity on Marketing Performance - Sharma, Piyush; Davcik, N.; Pillai, K. (Elsevier, 2016)
This study combines the signaling theory and dynamic marketing capabilities perspective to investigate the mediating role of product innovation in the influence of R&D expenditure and brand equity on marketing performance. The study shows that MNC firms are able to use R&D expenditure to improve their product innovation and market share to a greater extent compared to SME and retailer firms. However, the stronger brand equity of MNC firms may actually hurt the performance of their new products by inhibiting product innovation. The authors use regression and probit analysis to study a panel data for 1356 food brands. Overall, this research provides fresh insights into the process by which R&D expenditure and brand equity affect product innovation and marketing performance in highly competitive product categories.